Effects of Feeding Increasing Levels of Iron from Iron Sulfate or Iron Carbonate on Nursery Pig Growth Performance and Blood Criteria - H. E. Williams; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; J. Usry (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 140 weanling pigs (DNA 241 × 600, initially 12.2 ± 0.02 lb) were used in a 32-d study evaluating the effects of increasing dietary iron from either iron sulfate (FeSO4) or a micronized, agglomerated ferrous carbonate (FeCO3) on nursery pig growth performance and blood criteria. The micronized form of FeCO3is designed to improve nursery pig growth performance and blood iron status. Pigs used for this trial did not receive an iron injection after birth in order to increase sensitivity to added dietary iron. Pigs were weaned at approximately 21 d and were allotted to pens based on initial BW in a randomized complete block design with 5 pigs in each pen and 4 pens per treatment. Experimental treatments were arranged as a 2 × 3 + 1 factorial with main effects of dietary iron source (FeSO4vs. FeCO3) and level (10, 30, or 50 ppm) plus a negative control with no additional dietary iron. The basal diet was formulated to contain 40 ppm total dietary iron based on ingredient contributions and was formulated with an iron-free trace mineral premix. Experimental diets were formulated below the pigs’ recommended iron requirement based on National Research Council (NRC) estimates. Experimental diets were fed in pellet form for the duration of the trial. From d 0 to 32, there were no iron source × level interactions observed. Increasing iron improved (linear;P<0.05) average daily gain (ADG), average daily feed intake (ADFI), feed efficiency (F/G), hemoglobin (Hgb), and hematocrit (Hct). There was no evidence of difference (P>0.10) for an iron source effect on growth performance or blood criteria measured. Therefore, either iron source can be used in diets fed to weanling pigs without affecting performance.
Keywords: Ferrous carbonate; growth performance; iron; iron sulfate; nursery